Bizcocho encuentra un amigo - Capucilli, Alyssa Satin, 1957-; Schories, Pat; Pasternac, Susana (New York, NY : Rayo, 2008)
A puppy helps a little duck find its way home to the pond.
"Lectura compartida"--Cover.
Accelerated Reader
Yo se leer
Keywords: Dogs -- Juvenile fiction; Ducks -- Juvenile fiction; Perros -- Novela juvenil; Patos -- Novela juvenil